Gambaran Pengetahuan, Sikap dan Perilaku Penderita TB Paru dalam Minum Obat Anti Tuberculosis dengan Strategi Pengobatan di Wilayah Puskesmas Pondok Gede Bekasi Tahun 2013. - Widya Astuti; Herlina Herlina (STIKes Persada Husada Indonesia, 2016)
Indonesia is the fifth highest country with pulmonary TB patients in the world after India, China, South Africa, and Nigeria (WHO, 2009). World Health Organization, declared a global emergency on the subject of Pulmonary TB because,in the most countries it has been uncontrolled. Anti-TB drug resistance case is a difficult one to handle as it is not only more difficult and more expensive, but also has greater side effects with the unsatisfying result. The purpose of this study is to determine the overview of knowledge, attitudes, and behaviors of TB patients in taking anti-TB drugs with treatment successes in Public Health Center of Pondok Gede Bekasi. The study used a qualitative approach with design study case. Then, the sources of primary data in this study were obtained by interviewing informants and the public health center officers directly. Interviews were conducted in patients who have a history of positive pulmonary TB disease visiting the health center ( primary data) and observations. Furthermore, observations were carried out with the documents used in the implementation of the tuberculosis program. Meanwhile, secondary data were obtained by collecting the public health center written reports.The informants of this study are coordinators and person in charge of TB of the public health center. According to them, the strategy of TB treatment in the public healt h center is by implementing DOTS, Direct Observed Treatment Short-course. Furthermore, they consist of one male, knowledge about and one female, and there is different both of the informant pulmonary TB disease. In addition, it was found that the regularity and duration of the treatment effect on the success of the treatment of anti-TB